AI-ENHANCED MOBILE HEALTH APPLICATIONS FOR INTELLIGENT PATIENT MONITORING AND PERSONALIZED TREATMENT (Global Conference on Medical and Health Sciences, 2026)
The rapid proliferation of smartphones and mobile technologies has led to the emergence of mobile health (mHealth) as a critical component of modern healthcare systems. mHealth refers to the use of mobile devices, applications, and wireless technologies to support medical and public health practices. This study aims to evaluate the role of mHealth applications in patient monitoring, treatment adherence, and overall healthcare delivery. A mixed-methods research approach was employed, integrating quantitative analysis of clinical outcomes with qualitative insights from patients and healthcare professionals. The findings indicate that mHealth applications significantly improve patient engagement, enhance chronic disease management, and facilitate real-time monitoring of health conditions. Additionally, mHealth contributes to improved treatment adherence and reduced hospital readmissions. However, challenges such as data privacy, usability issues, and digital inequality remain significant barriers. The study concludes that mHealth applications have the potential to transform healthcare delivery by promoting personalized, accessible, and patient-centered care.
Keywords: mHealth, mobile health, digital health, patient monitoring, treatment adherence, healthcare technology, telehealth